Blood flow velocities in common carotid artery changes with age and exercise study by using of telemetry method - Noor Azmi, Azran Azhim; M., Katai; M., Akutagawa; Y., Hirao; K., Yoshizaki; S., Obara; M., Nomura; H., Tanaka; H., Yamaguchi; Y., Kinouchi (IEEE, 2006)
Measurement of blood flow velocity using Doppler ultrasound has become an important noninvasive tool not only in the diagnosis of cardiovascular disease but also in physiological measurement. Physiological blood flow velocities in common carotid artery (CCA) is altered markedly with advancing age. It is unknown that regular aerobic exercise training can alter and improve blood flow velocity waveforms in either healthy young or healthy older individuals. Blood flow velocities were measured in 89 putatively healthy volunteers with age range of 20-76 years: 65 subjects were sedentary and 24 subjects were regular exercise-trained. Blood flow velocity spectra were measured at resting using our newly developed portable telemetry Doppler ultrasound velocimeter (TDUV) with real-time monitoring. Blood flow velocity waveforms were obtained from the spectral blood flow velocities of instantaneous peak-velocities. As a result, blood flow in peak systolic SI, end-diastolic d, and peak diastolic velocities D decreased with aging by the following yearly rate: 7.18 mm/s/year, 2.64 mm/s/year, and 1.24 mm/s/year, respectively. Thus the indices of d/S1, S1/S2, and D/I had a significant change with age. However, resting heart rate (HR) and second systolic velocities S2 were not significantly changed with aging. Blood flow velocities in SI were higher in the exercise-trained, whereas S2, D, and d velocities had no difference between trained and sedentary adults. However, the index of D/I had a marked higher in exercise-trained adults. As anticipated to exercise effect, the resting heart rate (HR) were significantly lower in exercise-trained. There were no differential effects in three age-groups (P= NS, by multivariate analysis). In conclusion, an age-associated decrease blood flow velocities in CCA was altered and improved in the healthy middle-aged and older individuals who regularly performed aerobic exercise. The blood flow patterns in three age-groups design had no markedly change - - with age in regular aerobic exercise-trained adults. The adaptations of blood flow velocities to regular exercise were not different with aging.